PENGEMBANGAN WISATA LOKAL DI PESISIR MANGGAR KOTA BALIKPAPAN UNTUK PENINGKATAN PEREKONOMIAN MASYARAKAT SEKITAR - Hadiyatno, Didik; Indriastuty, Nina; Janah, Ulum (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. The eastern region of Balikpapan is dominated by fishing communities in Manggar. In this region, there are attractions Manggar Beach. The government and the surrounding community have used both elements in their daily activities. However, the utilization is still not maximal. Although the government has improved the coastal infrastructure, it is still necessary to develop human resources in order for the economy through tourism to materialize. Through strategic stages, namely (1) data collection; (2) analyzing data; (3) presentation of the result of data analysis, expected to get data to become picture and consideration of government and society around in improving economy area especially tourism with community profession partly as a fisherman. The findings in the tourism sector have yet to show results for the economy in Manggar. This is because the creativity and innovation of human resources have not been optimized by the community and local government. The potential of the community actually exists to be developed in the tourism sector. This can be done through training the management of fishery products by following the global development so as to attract domestic and foreign tourists, making the coastal area as a tourist destination of choice.Keywords: Development Of Tourism, Economy, Society Abstrak. Wilayah timur Balikpapan didominasi oleh masyarakat nelayan di Manggar. Di wilayah ini terdapat objek wisata Pantai Manggar. Pemerintah maupun masyarakat sekitar telah memanfaatkan kedua unsur tersebut dalam aktivitas keseharian. Namun, pemanfaatan tersebut masih belum maksimal. Walaupun pemerintah telah memperbaiki infrastruktur di pantai tersebut, masih perlu pengembangan SDM agar perekonomian melalui pariwisata dapat terwujud. Melalui tahapan strategis, yaitu (1) pengumpulan data; (2) penganalisisan data; (3) penyajian hasil analisis data, diharapkan diperoleh data-data untuk menjadi gambaran dan pertimbangan pemerintah serta masyarakat sekitar dalam meningkatkan perekonomian daerah khususnya pariwisata dengan profesi masyarakat sebagian sebagai nelayan. Hasil temuan di sektor pariwisata belum menampakkan hasil bagi perekonomian di Manggar. Hal tersebut dikarenakan kreatifitas dan inovasi SDM belum dioptimalkan oleh masyarakat dan pemerintah setempat. Potensi yang dimiliki masyarakat sebenarnya telah ada untuk dikembangkan di sektor pariwisata. Hal tersebut dapat dilakukan melalui pelatihan pengelolaan hasil perikanan dengan mengikuti perkembangan global sehingga menarik wisatawan dalam negeri maupun mancanegara, menjadikan wilayah pesisir sebagai tempat wisata pilihan.Kata Kunci: Pengembangan Wisata, Perekonomian, Masyarakat